2017
DOI: 10.1038/s41598-017-02629-9
|View full text |Cite
|
Sign up to set email alerts
|

Uneven distribution of complementary sex determiner (csd) alleles in Apis mellifera population

Abstract: The complementary sex determiner (csd) gene determines the sex of the western honey bee (Apis mellifera L.). Bees that are heterozygous at the csd locus develop into females; whereas hemizygous bees develop into males. The co-occurrence of two identical csd alleles in a single diploid genome leads to the genetic death of the bee. Thus, the maintenance of csd diversity in the population is favoured. The number and distribution of csd alleles is particularly interesting in light of the recent decline in the hone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 32 publications
(44 reference statements)
7
36
2
Order By: Relevance
“…Furthermore, one should remark that Page and Laidlaw based their analysis exclusively on considerations about the sex locus csd , which they assumed to have between 6 and 19 alleles in a population. In the meantime, it has been shown that this number is in reality at least one order of magnitude higher [ 94 ]. We therefore see across-family selection with appropriate selection rates, as presented in this study, as the more promising breeding alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one should remark that Page and Laidlaw based their analysis exclusively on considerations about the sex locus csd , which they assumed to have between 6 and 19 alleles in a population. In the meantime, it has been shown that this number is in reality at least one order of magnitude higher [ 94 ]. We therefore see across-family selection with appropriate selection rates, as presented in this study, as the more promising breeding alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, new alleles may appear continuously, as the HVR region is subject to a high level of recombination. As a result of such high levels of polymorphism, it is not surprising that the length and the exact position of the targeted HVR region show rather high levels of variability across these studies [7,9,11,18,21]. In order to retain the ability to compare all honey bee HVR sequences published thus far, we decided to target with our primers those conserved regions that were present in all sequences from the previous studies.…”
Section: Tracking Of Csd Alleles Offers Potential Benefits For Closedmentioning
confidence: 99%
“…These subspecies bear economic importance, out of which A. m. ligustica and A. m. carnica are kept worldwide commercially [15]. Several alleles of various honey bee subspecies were described based on the hypervariable (HVR) region [11,[16][17][18]. This particular region of the csd gene was selected for the typing of csd alleles in breeding programmes.…”
Section: Introductionmentioning
confidence: 99%
“…This fits perfectly with Dzierzon’s observations—hemizygous (unfertilized) eggs develop as males and heterozygous (fertilized) eggs developing as females. Homozygous eggs also develop as males, but these are rare because the diversity of csd alleles is high (there are hundreds of distinct alleles [3]), and workers discriminate against the homozygous larvae by eating them before they can develop [4]. A bee’s sex is thus a consequence of its genotype, falling squarely in the realm of “nature.”…”
Section: The Sex Genesmentioning
confidence: 99%